Epistemological Integration of Uṣul Fiqh and Blockchain: A Philosophical Approach to Digital Islamic Economic Ijtihad - Nursobah, Achmad (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study integrates the epistemology of uṣūl al-fiqh with blockchain ontology to formulate a digital ijtihad-maqaṣidī model relevant to the digital Islamic economy. The problem examined: how to develop an istinbāṭ methodology that is able to read and design laws in a blockchain algorithmic system? The novelty of this research lies in the combination of maqaṣid-driven ijtihad with technological architecture (smart contracts, digital identity, governance), a philosophical approach that has never been formulated systematically. The methods used are multi-methodological philosophical-normative: ontological analysis of technology, ushulī hermeneutics on nash and rules, and conceptual synthesis validated through thought experiments and expert panels; Data are derived from selected literature, fatwas, whitepapers, and case studies. The findings show three operational pillars (sharia design thinking; maqaṣid-guided algorithmic ethics; qawaʿid-based smart contracts) that enable the instilling of sharia values in system design. Implications: ijtihad becomes a proactive digital legal design tool and guideline for fatwas, regulators, and sharia fintech developers.